Aryne cycloaddition reaction as a facile and mild modification method for design of electrode materials for high-performance symmetric supercapacitor. (10th February 2021) - Sviridova, Elizaveta; Li, Min; Barras, Alexandre; Addad, Ahmed; Yusubov, Mekhman S.; Zhdankin, Viktor V.; Yoshimura, Akira; Szunerits, Sabine; Postnikov, Pavel S.; Boukherroub, Rabah
Abstract: Covalent modification of graphene-based materials can be considered as one of the most promising methods for tailoring their electrochemical properties and extending their application as electrode materials for supercapacitors. In this contribution, we report a facile and mild approach for the covalent functionalization of reduced graphene oxide (rGO) via aryne cycloaddition using pseudocyclic iodoxoborole as an aryne source. The structure and chemical composition of the functionalized rGO (f-rGO) were assessed by Fourier transform infrared (FTIR) spectroscopy, thermogravimetric analysis (TGA), ultraviolet–visible (UV–vis) spectrophotometry, Raman spectroscopy and X-ray photoelectron spectroscopy (XPS), which revealed the negligible influence of covalent modification on the rGO structure. Transmission electron microscopy (TEM) imaging showed an increase of the interlayer distance from 0.38 to 0.46 nm upon functionalization. The electrochemical performance of f-rGO material was studied by cyclic voltammetry (CV), galvanostatic charge-discharge (GCD) and electrochemical impedance spectroscopy (EIS) techniques in 2 M KOH aqueous solution as the electrolyte. Under optimized conditions, the f-rGO displayed a high specific capacitance of 297 F g −1 at a current density of 1 A g −1, which is much higher than that of unmodified rGO (170 F g −1 at 1 A g −1 ). Therefore, the f-rGO was used to construct a symmetric supercapacitor device, exhibiting an energy density of 6.7 Wh kg −1 at a power density of 685.8 W kg −1 . The device exhibited good cycling stability and ability to maintain about 96% of the initial capacitance value after 10, 000 cycles. Furthermore, two symmetric supercapacitor devices were successfully applied to power a home-designed windmill device for 3 s. The results obtained in the present study highlight the importance of graphene functionalization as an effective route to fabricate rGO-based materials with enhanced properties in energy storage devices. Graphical abstract: Image, graphical abstract